Antiferromagnet–ferromagnet transition in the cobaltites: Магнетизм - Troyanchuk, I.O.; Bushinsky, M.V.; Karpinsky, D.V.; Sirenko, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The three series oxygen-deficient cobaltites La0.5Ba0.5CoO3–δ, LnBaCo2O5.5 and Sr2YCo4O10.5 have been studied. It has been shown that La0.5Ba0.5CoO3 is an insulating ferromagnet whereas La0.5Ba0.5CoO2.75 is a pure antiferromagnet in which the oxygen vacancies are disordered. The oxygen-vacancies ordering leads to appearance of the ferromagnetic component apparently due to a formation of the noncollinear magnetic structure. The antiferromagnet–“ferromagnet” transition is accompanied by a giant magnetoresistance. It is suggested that in the ferromagnetic oxidized compounds Co3+ and Co4+ ions adopt intermediate spin state whereas for antiferromagnetic(Co4+-free) compositions Co3+ ions have high-spin state (pyramids CoO5) and dominant low-spin state (octahedra CoO6). In both ferromagnetic and antiferromagnetic compounds the superexchange via oxygen plays an essential role in a formation of the magnetic properties.